Comparative study of the synthetic methods for perylene-based covalent triazine polyimides. (February 2021) - Kim, Hong Mo; Jang, Ho Kyung; Hwang, Tae Gyu; Namgoong, Jin Woong; Kim, Jeong Yun; Yuk, Sim Bum; Lee, Jae Moon; Kim, Jae Pil
Abstract: Covalent organic framework (COF) is an emerging class of porous materials constructed by covalently linked building blocks including reactive organic functional groups. COFs are characterized by their ordered structures, high stability, and structural diversity. Covalent triazine framework (CTF) is a subclass of COFs, which consists of triazine building units. CTFs have attracted broad interests because of the large conjugated system with high nitrogen contents. Perylene derivative is one of the superior building units for practical applications of CTFs. Thus, in this work, we explored which synthetic strategy is appropriate for constructing the high-performance perylene based CTF by comparing two synthetic methods. The perylene-based triazine polyimides were synthesized by two different methods. The i -PTPI was synthesized by the imidization reaction which is one of the polycondensation reactions. The t -PTPI was synthesized by the acid-catalyzed trimerization reaction. The resultants showed significant differences in properties such as chemical composition, thermal stability, crystallinity and porosity even they consisted of the same building units because of these different synthesis routes. Consequently, this study proved that imidization method was more suitable to construct highly crystalline, porous and stable perylene-based CTF than the acid-catalyzed trimerization method. Graphical abstract: Image 1 Highlights: Two synthetic methods for the perylene-based covalent triazine framework have been proposed. Properties of resultants prepared by two methods have been compared. Microwave-assisted trimerization leads to the low crystallinity of product such as covalent triazine polyimide. Polyimidization method is the proper method for the synthesis of perylene-based covalent triazine frameworks.